DEODORO DA FONSECA A PROPAGANDA POLÍTICA DO PRIMEIRO PRESIDENTE DO BRASIL - Guimarães, Bruna Vieira (2007)
Study of politic history of the first president of Brazil, Manoel Deodoro da Fonseca, in the optics of the propaganda politics. The objectives had been to rescue the materials of propaganda used by the republican movement that culminated with the Announcement of the Republic commanded for Deodoro in 15 of November of 1889. And later, to understand the electoral process to which the general were chosen president for the congressmen, by means of the indirect vote, in day 25 of February of 1891. The adopted methodology was the Historical Research emphasizing the bibliographical and documentary study. Also they had been described published charges in the Revista Illustrada in the Provisory Government, the covering that the periodical O País made of the presidential election and the scene of censorship faced for the press. In the conclusion it consists that Deodoro did not make electoral campaign. Nor it needed, therefore in case that not he were elect, the Army to it would proclaim dictator. However, the deodoristas had convinced the members of the Congress and senators to vote in the marshal. Already, the opposition made campaign politics launching extra periodical edition spreading posters for the Federal Capital and approving repudiation motions of the situation candidacy. This election was simply a formality to keep Deodoro in the position most important of the country.(AU)